International oil policy - Safer, Arnold E.; Kennedy, Edward E. (Lexington, Mass. : Lexington Books, 1979)
The author discussed OPEC oil monopoly and its rising prices. He also proposed a broad and innovative agenda for America's national and international energy policy that deserves serious study.
Includes bibliographical references and index.
kjo 14/01/2019
Loans
Keywords: Energy policy; Petroleum industry and trade